The level of satisfaction of parents of students with learning disabilities in primary schools in Al-Madinah Al-Munawwarah region with the counseling services provided to their children - Alharbi, Ibrahim Ateeq; Yusef, Muhammad Abdulrahman (Journal of Educational and Psychological Sciences, 2022)
The aim of this study was to determine the level of satisfaction of parents of students with learning disabilities in Al-Madinah Al-Munawwarh region with the counseling services provided to their children. This study was followed the descriptive survey approach. The researcher created a questionnaire as a special tool for his study. The sample of study consisted of (327) parents of students with learning disabilities of various sexes, academic qualifications and ages in Al-Madinah region and its governorates.Findings showed that the level of satisfaction of parents of students with learning disabilities in Al-Madinah region with the counseling services given to their children was very high in the social, educational, and psychological dimensions, while it was high in the health dimension.There was a statistically significant difference between the study sample of parents of students with learning disabilities' satisfaction with the counseling services provided to their children in elementary schools according to the parent's educational level, which was represented in all dimensions and the average of the total of the questionnaire as a whole.When it came to determining the course of variation in the guardian's educational level, secondary and higher education came out on top, followed by university, diploma, and finally postgraduate studies.Also, there was a statistically significant difference according to the guardian's age group, as represented in the first dimension which is the social one. The direction was set in favor of more than 40 years, while there was no difference in the other dimensions, and no significant statistical differences among the responses of the sample of study according to gender was detected.The researcher came up with some conclusions of which the most important are paying more attention to the services offered to students with learning disabilities, and developing training programs for school counselors in dealing with students with learning disabilities.
Keywords: counseling services; learning disabilities; parents of students; satisfaction